INVESTIGATING THE ROLE OF MANF & CDNF IN THE PATHOPHYSIOLOGY OF PARKINSON’S DISEASE - Shawaf, Omar (My University, 2017)
CDNF and MANF are members of a recently discovered and evolutionarily conserved neurotrophic factor family implicated in supporting the survival and protection of midbrain dopaminergic neurons in the nigrostriatal pathway, which degenerate in Parkinson’s Disease (PD). Increasing evidence demonstrated that MANF overexpression resulted in significant protection and repair of TH+ cells and DA neurons in the substantia nigra (SN). In addition, continuous infusion of CDNF demonstrated greater protection of TH-positive neurons in the SNc and fibers in striatum than GDNF in the 6-OHDA neurotoxin model. Current literature suggests that CDNF and MANF are involved in regulating ER stress and are upregulated in vitro and in vivo during the unfolded protein response (UPR). Thus, this study sought to investigate whether selective knockdown (K/D) of MANF and CDNF causes pathophysiological conditions that lead to the behavioural manifestation of PD in preclinical models. Male Sprague-Dawley rats underwent stereotaxic surgery, whereby 2 μL at 0.5 μL/minute of MANF, CDNF, MANF and CDNF combined, or a scrambled negative control (N=44) of rat lentiviral-mediated shRNA formulations were infused into the SN in reference to bregma: Anterior/Posterior=-5.3 mm, Medial/Lateral=±2.3 mm, Dorsal/Ventral=-7.8 mm. Rats were tested on a battery of behavioural tests for the assessment of PD phenotypes, such as impairments in balance, gait and motor coordination. MANF K/D rats demonstrated PD phenotypes in the rearing duration, beam traversal, rotarod and cylinder test (P <0.05). These results were largely mirrored in the combined MANF and CDNF K/D group, however, CDNF K/D rats failed to demonstrate consistent motor deficits (P >0.05). Additionally, CDNF mRNA expression from the platelets of PD patients revealed no significant differences compared to healthy controls (P >0.05). In conclusion, the etiology of PD remains to be elucidated, and this is the first study to demonstrate that MANF K/D rats recapitulate key motor features of parkinsonism.
INVESTIGATING THE ROLE OF CEREBRAL DOPAMINE NEUROTROPHIC FACTOR (CDNF) & MESENCEPHALIC ASTROCYTE-DERIVED NEUROTROPHIC FACTOR (MANF) IN THE PATHOPHYSIOLOGY OF PARKINSON’S DISEASE
Keywords: MANF; CDNF; Parkinson's Disease; Neurotrophic; NTF; Pathophysiology